Penilaian Sejawat dalam Pembelajaran Kolaboratif: Perspektif Mahasiswa Teknologi Pangan Uniwara - Rafika Anisia Verdiyanti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Peer assessment is an evaluation method that involves students in assessing the performance of their peers. This study aims to explore the viewpoints of students of the Food Technology Study Program at Universitas PGRI Wiranegara towards the application of group assessment in a group context. The application of the peer assessment method is expected to provide a new perspective in a learning evaluation system that is more comprehensive and involves the active role of students. This qualitative research involved students from batch 2022 to 2024 with data collection through an online questionnaire. The results revealed three key findings: (1) students perceive peer assessment as a driver of increased responsibility and active participation in the group, (2) this method motivates students to contribute more optimally in group assignments, and (3) there are some challenges in the form of concerns about objectivity and potential conflicts between members. The findings provide important insights into how peer assessment can be implemented into the learning process to improve the quality of group work. The implications of this study suggest that peer assessment can be applied as an alternative evaluation method in various courses in the Food Technology Study Program to enhance collaborative learning.